Web-based home-hazard modification app for falls prevention: the views of those at risk of falling and their carers. Issue 3 (14th July 2020) - Holliday, Nikki; Ward, Gillian; Walker-Clarke, Aimee; Molitor, Rachael
Abstract : Purpose: The purpose of the study is to assess the usability and acceptability of FallCheck, a Web app that allows users to complete home-hazard assessments within their own home, with a group of people at risk of falling and their carers. Design/methodology/approach: This mixed method study used an online survey followed by semi-structured telephone interviews to collect both qualitative and quantitative data. A Think-Aloud study was used to test usability of the Web app through structured tasks. Findings: Findings showed that FallCheck was easy to use with few usability issues. The Web app was deemed appropriate to use by people at risk of falling (young or old) or by carers if appropriate. The depth of knowledge provision and breadth of content was acceptable, and many participants reported subsequently making changes to their home environment to reduce their risk of falling. Overall, the majority of participants reported feelings of improved confidence and safety with an increased awareness of fall risks and a reduction in fear of falling at home. Practical implications: FallCheck has good acceptability and usability with people at risk of falling and their carers and has the potential to improve access to home-hazard assessment and affect behavioural change regarding fall risk hazards and behaviour. Originality/value: This study describes successful use of an app that may be helpful in identifying home-hazards and making changes to reduce risk of falls, particularly in the absence of occupational therapy intervention and has the potential for integration into falls care pathways.